Finite element analysis of large deformations of hyperelastic solids in principal axes - Golovanov, Alexandr Ivanovich (Computational Continuum Mechanics, 2009)
The computing technology of analysis of hyperelastic solids in the finite strain regime is offered. As a working basis, the principal axes of the left stretch tensor are chosen. All relations necessary for finite-element formulation of the problem and its solution are constructed in terms of the principal stretches. Numerical examples are presented.